(untitled) (Scientific journal of the Fergana State University, 2026)
Indeed, every state has the right to immunity from the jurisdiction of another state. State immunity in civil law relations means that the state exercises its powers on the basis of legislation adopted by it, and the rights and obligations of the state in civil law relations are determined only in accordance with the legislation of this state. The article analyzes issues of state immunity as a subject of civil liability, including the UN Convention “On Jurisdictional Immunities of States and Their Property” As a result, certain conclusions were drawn.